Citrobacter O-antigens: structure of the O-antigenic polysaccharide from Citrobacter sp. 396. - Jann, B (1978)
The structure of the O-specific polysaccharide moiety of the lipopolysaccharide from Citrobacter 396 was elucidated by composition, methylation, and periodate oxidation studies. The repeating unit consists of four 2-linked mannoses and one 3-linked N-acetylglucosamine. One of the mannose units is substituted at C3 with alpha-glucose, and one is substituted at C3 with alpha-(2-O-acetyl)-abequose. All the mannosyl linkages appear to have the beta-configuration; the N-acetylglucosaminyl linkage has the alpha-configuration. In bacterial agglutination and passive hemagglutination in some Salmonella antisera, Citrobacter 396 as well as its O-antigenic lipopolysaccharide expressed the serological factors 5 and 6. In corroboration of our structural studies, this showed the presence of alpha-(2-O-acetyl)-abequosyl-1,3-mannose (factor 5) and alpha-glucosyl-1,3-mannose (factor 6).